2018
DOI: 10.1111/pce.13458
|View full text |Cite
|
Sign up to set email alerts
|

Defence‐related priming and responses to recurring drought: Two manifestations of plant transcriptional memory mediated by the ABA and JA signalling pathways

Abstract: Collective evidence from agricultural practices and from scientific research has demonstrated that plants can alter their phenotypic responses to repeated biotic and abiotic stresses or their elicitors. A coordinated reaction at the organismal, cellular, and genome levels has suggested that plants can "remember" an earlier stress and modify their future responses, accordingly. Stress memory may increase a plant's survival chances by improving its tolerance/avoidance abilities and may provide a mechanism for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 140 publications
(251 reference statements)
2
38
0
1
Order By: Relevance
“…Furthermore, the negative effects of elevated O 3 on the phloem-feeding behavior of B. tabaci was also absent in the 2-DDG-treated AC plants, which suggested that callose deposition contributed to O 3induced priming defense against B. tabaci. This is consistent with previous studies showing that preliminary reagent (e.g., indole-3-carboxylic acid and b-amino-butyric acid) treatmentinduced or abiotic stress (e.g., high silicon concentration)induced defense priming against subsequent insects or pathogen challenge is dependent on callose accumulation (Baccelli and Mauch-Mani, 2016;Yang et al, 2018;Avramova, 2019). In Arabidopsis, indole-3-carboxylic acid-and b-aminobutyric acid-induced callose priming against P. cucumerina infection is blocked in ABA-deficient mutants such as npq2, aba1-5, and aba2.3 (Ton and Mauch-Mani, 2004;Gamir et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the negative effects of elevated O 3 on the phloem-feeding behavior of B. tabaci was also absent in the 2-DDG-treated AC plants, which suggested that callose deposition contributed to O 3induced priming defense against B. tabaci. This is consistent with previous studies showing that preliminary reagent (e.g., indole-3-carboxylic acid and b-amino-butyric acid) treatmentinduced or abiotic stress (e.g., high silicon concentration)induced defense priming against subsequent insects or pathogen challenge is dependent on callose accumulation (Baccelli and Mauch-Mani, 2016;Yang et al, 2018;Avramova, 2019). In Arabidopsis, indole-3-carboxylic acid-and b-aminobutyric acid-induced callose priming against P. cucumerina infection is blocked in ABA-deficient mutants such as npq2, aba1-5, and aba2.3 (Ton and Mauch-Mani, 2004;Gamir et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…The interaction of JA with ABA has intensively been studied, particularly in response to recurring dehydration stress (Avramova, ). The plant's response to a first dehydration stress is mediated by both ABA and JA and induces transcriptional memory of drought‐inducible genes.…”
Section: Phytohormones: Mediating and Distributing The Stress Signalmentioning
confidence: 99%
“…Heat tolerance of plants can be induced or improved by stress or chemical priming (Savvides et al , Hossain et al ). Plants can ‘remember’ an earlier stress and modify their future responses to later stresses accordingly (Avramova ). Exposure of plants to mild or moderate drought, or drought priming of plants, can enhance plant tolerance to subsequent stresses, including drought, heat and cold (Li et al , Wang et al , Fleta‐Soriano and Munne‐Bosch ).…”
Section: Introductionmentioning
confidence: 99%